Contrastive Analysis of Phonology (Sounds, Speech, Stress, and Intonation) of Arabic and Indonesian Languages - Habiburrahman; Kurnia Wahyuni; Muhammad Mugni Assapari (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Phonology has a crucial role in the early stages of learning both native and foreign languages. This research aimed to analyze the phonological differences between Arabic and Indonesian, focusing on aspects such as sound systems, pronunciation, stress, and intonation. This study was classified as a literature review. The method employed was a descriptive contrastive analysis, comparing contrasting differences in Arabic and Indonesian through a pedagogical linguistic approach. The results showed that the vowel sounds in Arabic consist of fathah, fathah thowilah, kasrah, kasrah thowilah, dhommah, dhommah and thowilah which significantly impact the meaning of the language. On the other hand, Indonesian vowel sounds /i/, /u/, /e/, /ә/, /o/, and /a/ did not influence meaning and tended to remain consistent in their speech functions. Regarding stress and intonation, Indonesian utilized these elements to differentiate meaning when spoken with flat, high, and low tones in delivering news or interrogative sentences. In contrast, Arabic stress and intonation patterns were based on the position of consonants, syllables, and the length of vowels.